Rifaximin Ameliorates Non-alcoholic Steatohepatitis in Mice Through Regulating gut Microbiome-Related Bile Acids - Jian, Jie; Nie, Mei-Tong; Xiang, Baoyu; Qian, Hui; Yin, Chuan; Zhang, Xin; Zhang, Menghui; Zhu, Xuan; Xie, Wei-Fen (Frontiers in Pharmacology, 2022)
Non-alcoholic steatohepatitis (NASH) is the progressive stage of non-alcoholic fatty liver disease (NAFLD). The non-absorbable antibiotic rifaximin has been used for treatment of irritable bowel syndrome, traveling diarrhea, and hepatic encephalopathy, but the efficacy of rifaximin in NASH patients remains controversial. This study investigated the effects and underlying mechanisms of rifaximin treatment in mice with methionine and choline deficient (MCD) diet-induced NASH. We found that rifaximin greatly ameliorated hepatic steatosis, lobular inflammation, and fibrogenesis in MCD-fed mice. Bacterial 16S rRNA sequencing revealed that the gut microbiome was significantly altered in MCD-fed mice. Rifaximin treatment enriched 13 amplicon sequence variants (ASVs) belonging to the groups Muribaculaceae, Parabacteroides, Coriobacteriaceae_UCG-002, uncultured Oscillospiraceae, Dubosiella, Rikenellaceae_RC9_gut_group, Mucispirillum, and uncultured Desulfovibrionaceae. However, rifaximin treatment also reduced seven ASVs in the groups Aerococcus, Oscillospiraceae, uncultured Ruminococcaceae, Bilophila, Muribaculaceae, Helicobacter, and Alistipes in MCD-fed mice. Bile acid-targeted metabolomic analysis indicated that the MCD diet resulted in accumulation of primary bile acids and deoxycholic acid (DCA) in the ileum. Rifaximin delivery reduced DCA levels in MCD-fed mice. Correlation analysis further showed that DCA levels were associated with differentially abundant ASVs modulated by rifaximin. In conclusion, rifaximin may ameliorate NASH by decreasing ileal DCA through alteration of the gut microbiome in MCD-fed mice. Rifaximin treatment may therefore be a promising approach for NASH therapy in humans.